2018
DOI: 10.2147/jpr.s176475
|View full text |Cite|
|
Sign up to set email alerts
|

Population pharmacokinetic modeling of flurbiprofen, the active metabolite of flurbiprofen axetil, in Chinese patients with postoperative pain

Abstract: BackgroundFlurbiprofen axetil, a lipid-microsphere-carrier targeting preparation, is a non-steroidal anti-inflammatory drug indicated for the treatment of postoperative pain.AimThe aim of the study was to develop a population pharmacokinetic (PPK) model of flurbiprofen, the active metabolite of flurbiprofen axetil, and optimize the treatment of flurbiprofen axetil in Chinese patients.MethodsA total of 144 therapeutic drug-monitoring samples of flurbiprofen axetil from 72 patients were included in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The pharmacy manual of reference drug, flurbiprofen axetil injection (trade name, ROPION), describes the common adverse reactions as shock, allergy symptoms, acute renal failure, nephrotic syndrome, gastrointestinal bleeding and cramps, attacks of asthma, toxic epidermal necrolysis syndrome, skin and mucous membrane eye syndrome, exfoliative dermatitis, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (Al‐P) increases, etc. In this study, subject number 17 showed increased alanine aminotransferase activity after administration of the reference drug, which was in line with the above description of adverse drug reactions 9 . In addition, there was one case of nausea and two cases of epistaxis, which were very mild adverse drug reactions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The pharmacy manual of reference drug, flurbiprofen axetil injection (trade name, ROPION), describes the common adverse reactions as shock, allergy symptoms, acute renal failure, nephrotic syndrome, gastrointestinal bleeding and cramps, attacks of asthma, toxic epidermal necrolysis syndrome, skin and mucous membrane eye syndrome, exfoliative dermatitis, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (Al‐P) increases, etc. In this study, subject number 17 showed increased alanine aminotransferase activity after administration of the reference drug, which was in line with the above description of adverse drug reactions 9 . In addition, there was one case of nausea and two cases of epistaxis, which were very mild adverse drug reactions.…”
Section: Discussionsupporting
confidence: 88%
“…The following pharmacokinetic parameters were calculated according to the concentration versus blood collection time curves by using Winnonlin 7.0 and non‐compartment model 9 . C max and T max were the measured values, λz was the slope of the straight line at the end of the relative concentration‐time curve, and t 1/2 = 0.693/λz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most patients refused to endure the acute pain and requested post-operative analgesia in the preliminary experiment. In order to enhance the comfort level of patients and reduce doctor-patient disputes, patients in two groups were intravenously given flurbiprofen axetil (1 mg/kg) for post-operative analgesia at the end of the operation (40). The half-life of flurbiprofen axetil is ~5.8 h (41), and therefore, the pain within the first 6 h after the operation was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…p < 0.05 was considered statistically significant. Pharmacokinetic modeling was conducted with Drug and Statistics (DAS, version 2.0, Mathematical Pharmacology Professional Committee of China, Shanghai, China) using a one-compartment model (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%